LOCAL TAX REVENUE BEFORE AND AFTER THE IMPLEMENTATION OF ONLINE LOCAL TAX MONITORING TO INCREASE THE LOCAL GOVERNMENT REVENUE (PAD) OF SURAKARTA - Aris, Muhammad Abdul; Wijayanti, Arlinda; Fatchan, Ilham Nuryana (Universitas Muhammadiyah Surakarta, 2020)
Local governments are given the authority to manage their regional finances independently. One area that provides the biggest contribution in Local Revenue is local tax. For that reason, the regional government, especially the city of Surakarta, seeks to increase tax revenue, one of which is by implementing an online-based local tax monitoring system on regional self-assessment taxes. The purpose of this study was to analyze the differences in regional tax revenue before and after the implementation of online-based local tax monitoring in the context of increasing Surakarta City's Original Regional Revenue. The data in this study are secondary and primary data, secondary data including realization data and hotel tax targets, restaurant tax, and parking tax during the period October 2016-September 2018 which amounted to 24 data obtained from BPPKAD Surakarta City and primary data obtained from the results interview at BPPKAD Surakarta City. The analysis technique used to analyze data is descriptive statistics, and willcoxon signed rank test, using SPSS (Statistical Product and Service Solutions) tools. The results showed that by using the Wilcoxon signed rank test there were differences in tax revenues on hotel taxes, restaurant taxes, and parking taxes before and after the implementation of this online-based regional tax monitoring, sequentially 0.004 0.05, 0.002 0.05, and 0.002 0.05. The implementation of monitoring went quite well, as evidenced by the potential for tax leaks to be minimized which would automatically have an impact in increasing the original revenue of the city of Surakrta.